A simple method to separate cellulose-binding domains of fungal cellulases after digestion by a protease - Lemos, M. A. (2000)
Core-binding domains of fungal cellulases from Trichoderma reesei were purified using a new and simple technique. Cellulases were hydrolysed with papain and the binding domains were then separated from the digested mixture by ultrafiltration. The enzymatic digestion process was monitored using capillary electrophoresis. This methodology produced a yield of 85% of binding domains.